The Method of Hadith in Identifying Hoax Information - Mukhlis (Syntax Corporation Indonesia, 2022)
This study aims to discuss the bad impacts of hoaxes that some people intentionally convey hoax news. The warming of politics in Indonesia as accessed or found on social media by all levels of society triggers the rise of unclear news and cannot be accounted for. The method used in this research is to use a type of library research with a maudhu'i approach. Two sources of data were used, namely primary data sources and secondary data sources. This study describe the meaning of the hoax contained in the hadith of the Prophet Muhammad and explaination based on opinions of scholars hadith experts. The results of this study can be said that the Prophet Muhammad SAW in the hadith is strictly prohibited from spreading hoax news even if it is to joke or invite laughter. It is the same as being included in the group of people who spread hoax news because they are hypocrites, in the hadith of the Prophet Muhammad and offer a solution in dealing with this hoax news is to be persistent and not accept the news directly and with tawaqquf and not reject the news directly received.